2014
DOI: 10.1063/1.4869797
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance reversal in antiperovskite compound Mn3Cu0.5Zn0.5N

Abstract: We report detailed investigations of the structure, magnetic properties, electronic transport, and specific heat in Mn-based antiperovskite compounds Mn3Cu0.5Zn0.5N. Most strikingly, there are several fascinating features: (i) The magnetoresistance at 30 kOe (40 kOe) exceeds ∼1% (∼2%) over a temperature span of ∼70 K (∼25 K) from 5 to 140 K; (ii) magnetoresistance fluctuates at temperatures of 100–200 K, including an obvious sign reversal from negative to positive at ∼140 K. Analysis of the specific heat revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Antiperovskite manganese compounds Mn 3 AX (A ¼ main group and transitional elements; X ¼ N or C) have exhibited a variety of interesting physical properties, such as negative thermal expansion (NTE), 1-6 spin glass behavior, [33][34][35] giant magnetoresistance (GMR), [7][8][9] piezomagnetic effect, 10 magnetocaloric effect (MCE), 11 and near-zero temperature coefficient of resistivity (NZ-TCR), [12][13][14] due to their intrinsic characteristics, which involve strong correlations among lattice, spin, and charge degrees of freedom. 15 Experimental and theoretical investigations have suggested that the novel and unique physical properties are mainly associated with the complex magnetic structures, which can be tuned by chemical doping or element substitution.…”
Section: Introductionmentioning
confidence: 99%
“…Antiperovskite manganese compounds Mn 3 AX (A ¼ main group and transitional elements; X ¼ N or C) have exhibited a variety of interesting physical properties, such as negative thermal expansion (NTE), 1-6 spin glass behavior, [33][34][35] giant magnetoresistance (GMR), [7][8][9] piezomagnetic effect, 10 magnetocaloric effect (MCE), 11 and near-zero temperature coefficient of resistivity (NZ-TCR), [12][13][14] due to their intrinsic characteristics, which involve strong correlations among lattice, spin, and charge degrees of freedom. 15 Experimental and theoretical investigations have suggested that the novel and unique physical properties are mainly associated with the complex magnetic structures, which can be tuned by chemical doping or element substitution.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, Mn based antiperovskites have attracted considerable attention in terms of both fundamental research as well as potential technological applications. A first order magnetostructural transition found in these compounds is responsible for many such properties like, large magnetocaloric effect (MCE) [1,2,3], giant magnetoresistance (GMR) [4,5,6], the invar effect, giant negative thermal expansion [7], near zero temperature coefficient of resistance [8,9], magnetostriction [10] and piezomagnetic effects [11].…”
Section: Introductionmentioning
confidence: 99%
“…The considerable attention received by antiperovskite materials is due to the wide range of properties such as superconductivity 1,2 , giant magnetoresistance 3,4 , magnetostriction effect 5 , large magnetocaloric effect and giant negative thermal expansion (NTE) [6][7][8][9][10] demonstrated by them. The properties shown by these materials are associated with a first-order magnetostructural transition from paramagnetic or ferromagnetic to an antiferromagnetic state 6 .…”
Section: Introductionmentioning
confidence: 99%